Proceedings of International Symposium on Nuclear Astrophysics - Nuclei in the Cosmos - IX — PoS(NIC-IX) 2010
DOI: 10.22323/1.028.0198
|View full text |Cite
|
Sign up to set email alerts
|

About possible explanations to the lines of radioactive elements in the spectrum of Przybylski's star

Abstract: We made a short review of previous investigations of lines of short-lived radioactive elements in the spectrum of Przybylski's star (HD101065) and show that the best atmosphere model available today should be significantly improved. The synthetic spectra in the vicinities of lines of neutral and ionized technetium are calculated. Comparison of these spectra with high resolution VLT and IUE spectra permits to discuss the possibility of existence of technetium in the atmosphere of Przybylski's star.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…A similar result was reported by Bidelman (2005). Yushchenko et al (2006) found limits on the abundance of short-lived actinides in the atmosphere of HD 101065. Atmospheric modelling with new transition probabilities for a set of Pm lines ) and Ra and Ac lines ) supported the detection of these ions in HD 101065.…”
Section: Introductionmentioning
confidence: 97%
“…A similar result was reported by Bidelman (2005). Yushchenko et al (2006) found limits on the abundance of short-lived actinides in the atmosphere of HD 101065. Atmospheric modelling with new transition probabilities for a set of Pm lines ) and Ra and Ac lines ) supported the detection of these ions in HD 101065.…”
Section: Introductionmentioning
confidence: 97%
“…The resonance line 4297.06 Å, which is expected to be strongest from the lines we considered, should be present in the spectrum, but it is absent. Its calculated profile with the technetium abundance adopted by Yushchenko et al (2006), logϵ(Tc/H) 3.5 is in a huge discordance with the observed profile of this blend. The problem is shown in Figure 1 (see also discussion in Ryabchikova 2008, who made first such a conclusion).…”
Section: Spectrum Synthesismentioning
confidence: 71%
“…Yushchenko & Gopka (2004), in their overview, also mentioned the presence of the Tc lines in Przybylski's star. Yushchenko et al (2006) performed a more detailed examination of this problem. The synthetic spectrum technique was applied to fit the 4124.22 Å line of Tc I.…”
Section: Introductionmentioning
confidence: 99%